Association of Umbilical Cord Milking Versus Delayed Umbilical Cord Clamping With Death or Severe Intraventricular Hemorrhage Among Preterm Infants. Issue 3 (September 2020) - Katheria, A.; Reister, F.; Essers, J.; Mendler, M.; Hummler, H.; Subramaniam, A.; Carlo, W.; Tita, A.; Truong, G.; Davis-Nelson, S.; Schmölzer, G.; Chari, R.; et al.
Abstract : ( JAMA . 2019;322:1877–1886) Umbilical cord milking has been cited as an alternative to delayed umbilical cord clamping, which is the current standard of care. Like delayed umbilical cord clamping, umbilical cord milking provides placental transfusion that has been associated with neonatal benefits, including fewer deaths in preterm infants. The aim of this study was to examine whether umbilical cord milking was noninferior to delayed umbilical cord clamping in preterm infants.